Realism’s Kick - Massin, Olivier (Berlin: De Gruyter, 2020)
Samuel Johnson claimed to have refuted Berkeley by kicking a stone. It is generally thought that Johnson misses the point of Berkeley's immaterialism for a rather obvious reason: Berkeley never denied that the stone feels solid, but only that the stone could exist independently of any mind. I argue that Johnson was on the right track. On my interpretation, Johnson’s idea is that because the stone feels to resist our effort, the stone seems to have causal powers. But if appearances are to be taken at face value, as Berkeley insists, then the stone has causal powers. I argue that such causal powers threaten not only Berkeley’s view that only minds are active, but also, and more fundamentally, his central claim that sensible things depend on perception.
Keywords: Berkeley Realism Mind-independence Effort